Adrenergic signaling and oxidative stress: a role for sirtuins? - Corbi, Graziamaria; Conti, Valeria; Russomanno, Giusy; Longobardi, Giancarlo; Furgi, Giuseppe; Filippelli, Amelia; Ferrara, Nicola (Frontiers in Physiology, 2013)
The adrenergic system plays a central role in stress signaling and stress is often associated with increased production of ROS. However, ROS overproduction generates oxidative stress, that occurs in response to several stressors. β-adrenergic signaling is markedly attenuated in conditions such as heart failure, with downregulation and desensitization of the receptors and their uncoupling from adenylyl cyclase. Transgenic activation of β2-adrenoceptor leads to elevation of NADPH oxidase activity, with greater ROS production and p38MAPK phosphorylation. Inhibition of NADPH oxidase or ROS significantly reduced the p38MAPK signaling cascade. Chronic β2-adrenoceptor activation is associated with greater cardiac dilatation and dysfunction, augmented pro-inflammatory and profibrotic signaling, while antioxidant treatment protected hearts against these abnormalities, indicating ROS production to be central to the detrimental signaling of β2-adrenoceptors. It has been demonstrated that sirtuins are involved in modulating the cellular stress response directly by deacetylation of some factors. Sirt1 increases cellular stress resistance, by an increased insulin sensitivity, a decreased circulating free fatty acids and insulin-like growth factor (IGF-1), an increased activity of AMPK, increased activity of PGC-1a, and increased mitochondrial number. Sirt1 acts by involving signaling molecules such P-I-3-kinase-Akt, MAPK and p38-MAPK-β. βAR stimulation antagonizes the protective effect of the AKT pathway through inhibiting induction of Hif-1α and Sirt1 genes, key elements in cell survival. More studies are needed to better clarify the involvement of sirtuins in the β-adrenergic response and, overall, to better define the mechanisms by which tools such as exercise training are able to counteract the oxidative stress, by both activation of sirtuins and inhibition of GRK2 in many cardiovascular conditions and can be used to prevent or treat diseases such as heart failure.